Modern Infectious Diseases: Macroeconomic Impacts and Policy Responses - Bloom, David E.; Kuhn, Michael; Prettner, Klaus (Journal of Economic Literature, 2022)
We discuss and review literature on the macroeconomic effects of epidemics and pandemics since the late 20th century. First, we cover the role of health in driving economic growth and well-being and discuss standard frameworks for assessing the economic burden of infectious diseases. Second, we sketch a general theoretical framework to evaluate the tradeoffs policymakers must consider when addressing infectious diseases and their macroeconomic repercussions.In so doing, we emphasize the dependence of economic consequences on (i) disease characteristics; (ii) inequalities among individuals in terms of susceptibility, preferences, and income; and (iii) cross-country heterogeneities in terms of their institutional and macroeconomic environments. Third, we study pharmaceutical and nonpharmaceutical policies aimed at mitigating and preventing infectious diseases and their macroeconomic repercussions. Fourth, we discuss the health toll and economic impacts of five infectious diseases:HIV/AIDS, malaria, tuberculosis, influenza, and COVID-19. Although major epidemics and pandemics can take an enormous human toll and impose a staggering economic burden, early and targeted health and economic policy interventions can often mitigate both to a substantial degree.